Antibacterial properties of Cu-doped TiO2 prepared by chemical and heat treatment of Ti metal. Issue 4 (2nd October 2021) - Suzuki, Kanae; Yokoi, Taishi; Iwatsu, Misato; Furuya, Maiko; Yokota, Kotone; Mokudai, Takayuki; Kanetaka, Hiroyasu; Kawashita, Masakazu
ABSTRACT: In this study, we proposed Cu-doped TiO2, prepared by the alkaline and heat treatment of titanium (Ti) metal, for use in dental applications because of its bone-bonding and antibacterial properties generated by the release of Cu ions and visible-light-responsive photocatalysis. We successfully prepared Cu-doped TiO2 on a Ti chip surface with a Cu content of 7 at.%. The apatite-forming ability of the Cu-doped TiO2 was evaluated using a simulated body fluid and it was found that apatite formation occurred. Hence, we concluded that Cu-doped TiO2 exhibits bone-bonding properties. The antibacterial properties of Cu-doped TiO2 for Escherichia coli were higher than those of non-doped TiO2 under visible light irradiation. The enhanced antibacterial effect was mainly caused by the visible-light-responsive photocatalysis of Cu-doped TiO2 . We confirmed that the reactive oxygen species generated by the visible-light-responsive photocatalysis of Cu-doped TiO2 were hydroxyl radicals formed by the reaction of hydroxide ions (OH − ) and holes (h + ). Our findings are useful for the development of novel bioactive TiO2 -based coatings and bulk materials with antibacterial properties by Cu doping.